Qos-Aware Handover Scheme for Hierarchical Mobile Ipv6 Using Context Transfer with Link Layer Trigger - N. Pillay, Shamini Pillay (2004)
The incredible rate that the Internet is growing has made recently for the convergence of the various networks into an unified IP based architecture. The challenge in such a complex network is to provide a seamless support. Seamless handover is a combination of fast and smooth handover. Thus seamless handover will basically offer lower latency and packet drops. In this study, we examine a QoS-aware handover scheme based on Hierarchical Mobile IPv6 architecture. Enhancements to the scheme to improve seamless support are investigated. The two main elements added to this system are the use of link layer trigger and context transfer. The detection and triggering of handover is an important functionality of handover, which has a strong impact on its performance in terms of handover latency and packet loss. Link layer trigger shortens the time for handover detection and therefore decrease the overall service interruption caused by handover. The main purpose of context transfer is to reduce the time when a particular flow does not receive the contracted QoS due to a handover situation. This is achieved by transferring in advance the information to the access router where the mobile node is expected to be attaching next in order to maintain the QoS for that flow. Without context transfer, the access router takes some time to recover this information due to the exchange of signaling information. The time wasted here can be harmful for real-time applications that require timely delivery and a constant service level. Apart from this, context transfer is also a way to preserve scarce wireless bandwidth between mobile node and the access router, as it does not use this wireless link to reinitiate QoS information as done previously in the QoS-aware handover scheme. The proposed scheme performance is proven by means of simulation and an analytical study, whereby handover delay and packet loss are the main performance parameters. Simulation results have proved that the proposed scheme performs better by decreasing the handover delay by 75 % and packet loss rate by 16.3 %. Further the analytical study done validates the results obtain from simulation by proving analytically the decrease in handover delay, packet loss and utilization of bandwidth